2006
DOI: 10.1017/joh2006369
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil cationic protein, specific IgE and IgG4 in human toxocariasis

Abstract: Among 67 French patients presenting a toxocaral infection, various demographic, environmental, clinical and laboratory parameters (blood eosinophil count, eosinophil cationic protein (ECP), serum total IgE, specific IgE against common inhalant allergens, specific IgE and IgG4 against Toxocara excretory-secretory antigens) were investigated. Correlation studies and logistic regression analyses were conducted, testing elevated levels of ECP, specific anti-Toxocara IgE or IgG4 as outcome variables An elevated ECP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
0
15
0
3
Order By: Relevance
“…Distinct mechanisms may be responsible for the diverse parasites. For example, the production of specific IgE against parasites has been shown for Toxocara [21] or Anisakis simplex [22]. Although some studies or case reports indicated high total IgE and/or parasite-specific IgE values in chronic urticaria patients infected with Giardia [23] or B. hominis [24], other studies reported no difference in total IgE levels between patients who had the same parasites and healthy controls [18].…”
Section: Discussionmentioning
confidence: 99%
“…Distinct mechanisms may be responsible for the diverse parasites. For example, the production of specific IgE against parasites has been shown for Toxocara [21] or Anisakis simplex [22]. Although some studies or case reports indicated high total IgE and/or parasite-specific IgE values in chronic urticaria patients infected with Giardia [23] or B. hominis [24], other studies reported no difference in total IgE levels between patients who had the same parasites and healthy controls [18].…”
Section: Discussionmentioning
confidence: 99%
“…Büyürken oluşturdukları karaciğer hasarına bağlı olarak, fonksiyonlarında bozulma meydana gelebileceği bilinmektedir. Yapılan çalışmalarda, KE'li hastalarda ALT ve AST düzeylerinin arttığı gösterilmiş, karaciğer enzim yüksekliği-nin dokuda meydana gelen lokal eozinofi li ile ilişkili olabileceği bildirilmiştir [27][28][29] . Bizim çalışmamızda, tanı sırasında biyokimya parametreleri içinde GGT yüksekliği (%28) belirgin olup bunu ALT (%16), AST (%16) ve ALP (%13) yüksekliği takip etmiştir.…”
Section: şEkil 4 Seropozitif Ke öN Tanılı (N= 32) Ve Seronegatif Anunclassified
“…Reflecting on these findings, it could be mentioned that urticaria is a skin manifestation, related to helminths or arthropods with a cutaneous phase: Schistosoma, Sarcoptes scabiei, as well as ticks and other blood sucking arthropods have been involved in Th2-based immunologic mechanisms [37,38]. Among patients with toxocariasis, an elevated eosinophil cationic protein (ECP) level was significantly associated with both cough and rhinitis, a high level of specific anti-toxocara IgE with itchy rashes [39]. Loeffler's syndrome, which resembles the pathophysiological features of chronic asthma with its Th2-related immunologic feature, is related to Ascaris and Necator infection, both of which have an obligatory pulmonary phase [40].…”
Section: Host-parasite Interaction and Parasito-sis-urticaria Relatiomentioning
confidence: 99%